PERFORMANCE OF THE INTERAGENCY WORKING GROUP ON INTRODUCTION OF AT THE BELARUS’ MACHINE-BUILDING ENTERPRISES ROLL PRODUCTS MANUFACTURED AT OJSC BSW - P. A. Vityaz; A. V. Tolstoy; A. V. Vengura (Литьë и металлургия, 2017)
Information on results of a meeting of the Interagency working group on introduction to machine-building enterprises of Republic of Belarus of roll products manufactured at ОJSC «BSW – Management Company of Holding «BMC», which are made in accordance to the European norms is provided. The purposes, tasks and activities of this working group are presented. Opinions of participants of a meeting are stated.